Electrolyte, preparation method thereof and lithium ion battery
By adding additive A containing imidazole groups to the electrolyte of a ternary high-voltage lithium-ion battery, the problems of solvent oxidation and hydrofluoric acid erosion under high voltage conditions are solved, and the stability and circulation performance of the battery interface film are improved.
Patent Information
- Application Number
- CN202411759340.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-12-02
AI Technical Summary
Under high voltage conditions of ternary high voltage lithium-ion batteries, the solvent in the electrolyte is easily oxidized and decomposed, causing hydrofluoric acid to erode the positive electrode and dissolution of transition metal ions, which seriously limits the performance and use of the positive electrode material.
A specific additive A is added to the electrolyte. The structure of additive A includes imidazole groups, which can participate in the film formation of the positive electrode and the negative electrode, generate stable interface films such as lithium nitride, reduce the dissolution of transition metal ions, and adsorb water and corrosive substances through the plane conjugation effect.
By adding additive A, the stability of the solid electrolyte interface film is improved, the side reaction between water, gas and corrosive substances and battery components is reduced, the dissolution of transition metal ions is reduced, and the high-temperature storage and cycling performance of the battery is improved.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to an electrolyte, a preparation method thereof and a lithium ion battery. Background Art
[0002] In recent years, ternary cathode materials have been applied to power batteries of new energy vehicles. However, under high voltage conditions (>4.3V), the solvent in the electrolyte is prone to oxidative decomposition on the surface of the cathode material. The hydrogen ions produced by the oxidative decomposition of the solvent are prone to react with the hexafluorophosphate ions in the electrolyte to form hydrofluoric acid. The hydrofluoric acid corrodes the cathode, causing the transition metal of the cathode to dissolve, and water and gas to be produced inside the battery, which seriously limits the performance and use of the cathode material.
[0003] In the related art, the electrolyte of the ternary high-voltage battery system (>4.3V) generally contains additives such as hexamethyldisilazane (HMDS), dicyclohexylcarbodiimide (DCC), and trimethylsilyl phosphate (TMSP). Although these additives have an acid-removing effect, when used as electrolyte additives, they often lead to deterioration of the battery cycle performance.
[0004] Therefore, it is necessary to develop an electrolyte suitable for the ternary high-voltage battery system to improve the battery's cycle performance and storage performance. Summary of the invention
[0005] The embodiments of the present invention provide an electrolyte and a preparation method thereof and a lithium-ion battery, which can improve the technical problems of poor electrolyte cycle performance and storage performance.
[0006] In a first aspect, an embodiment of the present invention provides an electrolyte, wherein the electrolyte comprises an organic solvent, an additive and a lithium salt, wherein the additive comprises an additive A, and the structure of the additive A is shown in Formula I:
[0007]
[0008] wherein n is selected from 0, 1, 2, 3, 4, 5 or 6;
[0009] The substituents R1, R2 and R3 are each or independently selected from a hydrogen atom, a halogen, a cyano group, an isocyanate group, a C1-C10 straight or branched alkyl group, a C1-C10 straight or branched alkoxy group, a C1-C10 halogenated straight or branched alkyl group, a C1-C10 halogenated straight or branched alkoxy group, a C3-C10 straight or branched carboxylate group, a C3-C10 straight or branched alkenyl group, a C3-C10 straight or branched alkynyl group, a C6-C26 unsubstituted aryl group, a C6-C26 aryl group substituted by an alkyl group, a hydroxyl group and / or a halogen group, a C7-C27 unsubstituted benzyl group, a C7-C27 benzyl group substituted by an alkyl group, a hydroxyl group and / or a halogen group, or a combination of these groups.
[0010] In one embodiment, n is selected from 0, 1 or 2; and / or
[0011] The substituents R1, R2 and R3 are each or independently selected from a hydrogen atom and / or a C1-C2 straight-chain alkyl group.
[0012] In one embodiment, the mass percentage of the additive A in the electrolyte is 0.2%-2.0%; and / or
[0013] The additive A is selected from at least one of imidazole-1-ylacetonitrile, 2-(2-methyl-1H-imidazol-1-yl)acetonitrile, 2-(2-ethyl-1H-imidazol-1-yl)acetonitrile, 1H-imidazole-1-carbonitrile, N-(2-cyanoethyl)imidazole, and 1-cyanoethyl-2-methylimidazole.
[0014] In one embodiment, the additives further include carbonate additives, sulfur-containing additives and lithium salt additives.
[0015] In one embodiment, the mass percentage of the carbonate additive in the electrolyte is 0.2%-1.0%; and / or
[0016] The mass percentage of the sulfur-containing additive in the electrolyte is 0.2%-2.0%; and / or
[0017] The mass percentage of the lithium salt additive in the electrolyte is 0.5%-2.0%; and / or
[0018] The carbonate additive includes at least one of vinylene carbonate, fluoroethylene carbonate and vinyl carbonate; and / or
[0019] The sulfur-containing additive includes at least one of 1,3-propane sultone, 1,3-propylene sultone, vinyl sulfate, and methylene disulfonate; and / or
[0020] The lithium salt additive includes at least one of lithium difluorobisoxalatoborate, lithium difluorobisoxalatophosphate, lithium bisoxalatoborate, lithium fluorosulfonyl imide, lithium difluorophosphate, and lithium tetrafluoroborate.
[0021] In one embodiment, the mass percentage of the lithium salt in the electrolyte is 10%-16%; and / or
[0022] The lithium salt includes at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide and lithium tetrafluoroborate.
[0023] In one embodiment, the organic solvent includes at least two of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and fluoroethylene carbonate.
[0024] In one embodiment, in the organic solvent, the volume fraction of ethylene carbonate is 0 - 30%, the volume fraction of propylene carbonate is 0 - 20%, the volume fraction of dimethyl carbonate is 0 - 40%, the volume fraction of diethyl carbonate is 0 - 20%, the volume fraction of ethyl methyl carbonate is 0 - 50%, and the volume fraction of fluoroethylene carbonate is 0 - 20%.
[0025] Second, an embodiment of the present invention provides a method for preparing the electrolyte as described above, and the method includes the following steps:
[0026] Under a protective atmosphere, the formulated amounts of the organic solvent, lithium salt, and additive are mixed evenly to obtain the electrolyte;
[0027] Among them, the additive includes additive A.
[0028] In one embodiment, the order of adding the mixed raw materials is to add the additive to the organic solvent, and then add the lithium salt; and / or
[0029] The protective atmosphere includes a nitrogen atmosphere and / or an argon atmosphere; and / or
[0030] The additive further includes a carbonate additive, a sulfur-containing additive, and a lithium salt additive.
[0031] Third, an embodiment of the present invention provides a lithium-ion battery, and the lithium-ion battery includes the electrolyte as described above.
[0032] In one embodiment, the lithium-ion battery further includes a positive electrode, a negative electrode, and a separator;
[0033] The active material of the positive electrode is a nickel cobalt manganese ternary material; and / or
[0034] The active material of the negative electrode is graphite or silicon carbon.
[0035] In one embodiment, the chemical formula of the nickel cobalt manganese ternary material is: Li(Ni x Co y Mn z )O2, where 0.5 ≤ x < 0.9, 0 < y ≤ 0.3, 0 < z ≤ 0.3, and x + y + z = 1.
[0036] The beneficial effects of the embodiments of the present invention:
[0037] In an embodiment of the present invention, by adding additive A to the electrolyte, the imidazole group in additive A enables additive A to participate in positive electrode film formation and negative electrode film formation, and the generated solid electrolyte interface film component includes lithium nitride, which can improve the stability of the solid electrolyte interface film; in addition, the carbon-carbon double bond and the carbon-nitrogen double bond in the imidazole group in additive A are bonded in an SP2 hybridization manner, so that additive A has a planar conjugation effect, can be delocalized and can be used as a Lewis base to capture H2O and corrosive substances such as phosphorus pentafluoride and hydrofluoric acid in the battery, thereby reducing the side reactions of water, gas and corrosive substances with other components in the battery; in addition, the cyano, cyanoethyl or dimethylene cyano groups directly connected to the nitrogen atom in the imidazole group in additive A can not only participate in positive electrode film formation, but also coordinate with transition metal ions in the positive electrode material to reduce the dissolution of transition metal ions. At the same time, the cyano, cyanoethyl or dimethylene cyano groups can be used as Lewis bases to adsorb hydrofluoric acid. Additive A can improve the stability of the positive and negative solid electrolyte interface films, reduce the side reactions between water, gas and corrosive substances and other components in the battery, reduce the dissolution of transition metal ions, and thus improve the high temperature storage performance and cycle performance of the battery. DETAILED DESCRIPTION
[0038] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention. In the present invention, unless otherwise specified, the directional words used, such as "upper" and "lower", generally refer to the upper and lower parts of the device in actual use or working state; while "inside" and "outside" refer to the outline of the device.
[0039] In the related art, the electrolyte cycle performance and storage performance of lithium-ion batteries are poor and need to be further improved.
[0040] To solve the above problems, an embodiment of the present application provides an electrolyte, the electrolyte comprising an organic solvent, an additive and a lithium salt, the additive comprising an additive A, and the structure of the additive A is shown in Formula I:
[0041]
[0042] wherein n is selected from 0, 1, 2, 3, 4, 5 or 6;
[0043] The substituents R1, R2 and R3 are each or independently selected from a hydrogen atom, a halogen, a cyano group, an isocyanate group, a C1-C10 straight or branched alkyl group, a C1-C10 straight or branched alkoxy group, a C1-C10 halogenated straight or branched alkyl group, a C1-C10 halogenated straight or branched alkoxy group, a C3-C10 straight or branched carboxylate group, a C3-C10 straight or branched alkenyl group, a C3-C10 straight or branched alkynyl group, a C6-C26 unsubstituted aryl group, a C6-C26 aryl group substituted by an alkyl group, a hydroxyl group and / or a halogen group, a C7-C27 unsubstituted benzyl group, a C7-C27 benzyl group substituted by an alkyl group, a hydroxyl group and / or a halogen group, or a combination of these groups.
[0044] In this embodiment, by adding additive A to the electrolyte, the imidazole group in additive A enables additive A to participate in positive electrode film formation and negative electrode film formation, and the generated solid electrolyte interface film components include lithium nitride, which can improve the stability of the solid electrolyte interface film; in addition, the carbon-carbon double bond and the carbon-nitrogen double bond in the imidazole group in additive A are bonded in an SP2 hybridization manner, so that additive A has a planar conjugation effect, can be delocalized and can act as a Lewis base to capture H2O and corrosive substances such as phosphorus pentafluoride and hydrofluoric acid in the battery, thereby reducing side reactions between water, gas and corrosive substances and other components in the battery.
[0045] In this embodiment, the structure of additive A also includes groups such as cyano, cyanoethyl or dimethylene cyano directly connected to the nitrogen atom of the imidazole group. In addition to participating in the positive electrode film formation, groups such as cyano, cyanoethyl or dimethylene cyano can also coordinate with transition metal ions in the positive electrode material to reduce the dissolution of transition metal ions. At the same time, groups such as cyano, cyanoethyl or dimethylene cyano can act as a Lewis base to adsorb hydrofluoric acid.
[0046] In one embodiment, n is selected from 0, 1 or 2; and / or, the substituents R1, R2 and R3 are each or independently selected from a hydrogen atom and / or a C1-C2 straight-chain alkyl group.
[0047] Optionally, the additive A is selected from at least one of imidazol-1-yl acetonitrile, 2-(2-methyl-1H-imidazol-1-yl)acetonitrile, 2-(2-ethyl-1H-imidazol-1-yl)acetonitrile, 1H-imidazole-1-carbonitrile, N-(2-cyanoethyl)imidazole, and 1-cyanoethyl-2-methylimidazole. On the one hand, these substances can improve the high temperature storage performance and cycle performance of the battery; on the other hand, these substances can be directly purchased commercially, and the raw materials are easily available, which can save the synthesis steps of the additive A and simplify the production process of the electrolyte.
[0048] In one embodiment, the mass percentage of additive A in the electrolyte is 0.2%-2.0%. Optionally, the mass percentage of additive A in the electrolyte is any one of 0.2%, 0.5%, 0.8%, 1.0%, 1.2%, 1.5%, 1.8%, 2.0%, etc., or a range between any two. In the present invention, if the amount of additive A is too little, the effect of additive A on effectively adsorbing H2O, phosphorus pentafluoride, hydrofluoric acid and other substances is not ideal; if the amount of additive A is too much, it is easy to cause the battery impedance to increase.
[0049] In one embodiment, the additives also include carbonate additives, sulfur-containing additives and lithium salt additives. Among them, carbonate additives can form a film at the negative electrode; lithium salt additives have the function of forming films at both the positive and negative electrodes, and the generated solid electrolyte interface film is relatively dense, which can inhibit the dissolution of positive electrode metal ions, weaken the damage of additive A and metal ions to the negative electrode solid electrolyte interface film, thereby reducing the deterioration of additive A on the negative electrode and improving the stability of film formation; sulfur-containing additives can assist in film formation at both the positive and negative electrodes, and have high thermal stability. The present invention can further improve the high-temperature storage performance and cycle performance of the battery by adding carbonate additives, sulfur-containing additives, lithium salt additives and additive A, and utilizing the synergistic effect between the additives.
[0050] In one embodiment, the carbonate additive includes at least one of vinylene carbonate, fluoroethylene carbonate, and vinyl vinyl carbonate.
[0051] In one embodiment, the sulfur-containing additive includes at least one of 1,3-propane sultone, 1,3-propylene sultone, vinyl sulfate, and methylene disulfonate.
[0052] In one embodiment, the lithium salt additive includes at least one of lithium difluorobisoxalatoborate, lithium difluorobisoxalatophosphate, lithium bisoxalatoborate, lithium fluorosulfonyl imide, lithium difluorophosphate, and lithium tetrafluoroborate.
[0053] In one embodiment, the mass percentage of the carbonate additive in the electrolyte is 0.2%-1.0%. Optionally, the mass percentage of the carbonate additive in the electrolyte can be any one of 0.2%, 0.4%, 0.6%, 0.8%, 1.0%, etc. or a range between any two. In the present invention, if the content of the carbonate additive is too little, the effect of forming a dense solid electrolyte interface film is not ideal; if the content of the carbonate additive is too much, it is easy to cause impedance to be too large and aggravate high-temperature gas production.
[0054] In one embodiment, the mass percentage of the sulfur-containing additive in the electrolyte is 0.2%-2.0%. Optionally, the mass percentage of the sulfur-containing additive in the electrolyte can be any one of 0.2%, 0.5%, 0.8%, 1.0%, 1.2%, 1.5%, 1.8%, 2.0%, etc., or a range between any two. In the present invention, if the content of the sulfur-containing additive is too little, the effect of forming a dense solid electrolyte interface film is not ideal; if the content of the sulfur-containing additive is too much, it is easy to cause excessive film formation and a decrease in battery cycle performance.
[0055] In one embodiment, the mass percentage of the lithium salt additive in the electrolyte is 0.5%-2.0%. Optionally, the mass percentage of the lithium salt additive in the electrolyte can be any one of 0.5%, 0.8%, 1.0%, 1.2%, 1.5%, 1.8%, 2.0%, etc., or a range between any two. In the present invention, if the content of the lithium salt additive is too little, the effect of forming a dense solid electrolyte interface film is not ideal; if the content of the lithium salt additive is too much, it is easy to cause gas production and electrical performance degradation.
[0056] In one embodiment, the lithium salt includes at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, and lithium tetrafluoroborate.
[0057] In one embodiment, the mass percentage of the lithium salt in the electrolyte is 10%-16%. Optionally, the mass percentage of the lithium salt in the electrolyte can be any one of 10%, 11%, 12%, 13%, 14%, 15%, 16%, etc., or a range between any two.
[0058] In one embodiment, the organic solvent includes at least two of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and fluoroethylene carbonate.
[0059] In one embodiment, the volume fraction of ethylene carbonate in the organic solvent is 0-30%. Optionally, the volume fraction of ethylene carbonate in the organic solvent can be any one of 0, 5%, 10%, 15%, 20%, 25%, 30%, etc. or a range between any two.
[0060] In one embodiment, the volume fraction of propylene carbonate in the organic solvent is 0-20%. Optionally, the volume fraction of propylene carbonate in the organic solvent can be any one of 0, 5%, 10%, 15%, 20%, etc. or a range between any two.
[0061] In one embodiment, the volume fraction of dimethyl carbonate in the organic solvent is 0-40%. Optionally, the volume fraction of dimethyl carbonate in the organic solvent can be any one of 0, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, etc. or a range between any two.
[0062] In one embodiment, the volume fraction of diethyl carbonate in the organic solvent is 0-20%. Optionally, the volume fraction of diethyl carbonate in the organic solvent can be any one of 0, 5%, 10%, 15%, 20%, etc. or a range between any two.
[0063] In one embodiment, the volume fraction of ethyl methyl carbonate in the organic solvent is 0-50%. Optionally, the volume fraction of ethyl methyl carbonate in the organic solvent can be any one or any two of 0, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% etc.
[0064] In one embodiment, the volume fraction of fluoroethylene carbonate in the organic solvent is 0-20%. Optionally, the volume fraction of fluoroethylene carbonate in the organic solvent can be any one of 0, 5%, 10%, 15%, 20%, etc. or a range between any two.
[0065] The present application also provides a method for preparing the electrolyte as described above, comprising the following steps:
[0066] S1. Under a protective atmosphere, uniformly mix the organic solvent, lithium salt and additives in the formula to obtain an electrolyte, wherein the additives include additive A. The preparation method provided by the present invention is simple to operate and has a short process, and can meet the needs of industrial large-scale production.
[0067] As a preferred technical solution of the present invention, the additives also include carbonate additives, sulfur-containing additives and lithium salt additives in a formulated amount.
[0068] In one embodiment, the order of adding the mixed raw materials is adding the additive to the organic solvent and then adding the lithium salt.
[0069] In one embodiment, the protective atmosphere includes a nitrogen atmosphere and / or an argon atmosphere.
[0070] The present application also provides a lithium-ion battery, which includes the electrolyte as described above.
[0071] In one embodiment, the lithium ion battery further comprises a positive electrode, a negative electrode and a separator.
[0072] Preferably, the active material of the positive electrode is a nickel-cobalt-manganese ternary material.
[0073] Preferably, the active material of the negative electrode is graphite or silicon carbide.
[0074] In one embodiment, the chemical formula of the nickel-cobalt-manganese ternary material is: Li(Ni x Co y Mn z )O2, where 0.5 ≤ x < 0.9, 0 < y ≤ 0.3, 0 < z ≤ 0.3, and x + y + z = 1.
[0075] The above solution will be further described below in conjunction with specific examples, and the preferred embodiments of the present application are described in detail as follows:
[0076] Example 1
[0077] This example provides an electrolyte, which is composed of an organic solvent, a lithium salt, a carbonate additive, a sulfur-containing additive, a lithium salt additive, and additive A;
[0078] Among them, the lithium salt is lithium hexafluorophosphate, and its mass percentage in the electrolyte is 12.5%;
[0079] The carbonate additive is vinylene carbonate, and its mass percentage in the electrolyte is 0.5%;
[0080] The lithium salt additive is lithium difluorobis(oxalato)borate, and its mass percentage in the electrolyte is 1.0%;
[0081] The sulfur-containing additive is ethylene sulfate, and its mass percentage in the electrolyte is 1.0%;
[0082] Additive A is imidazol-1-ylacetonitrile, and its mass percentage in the electrolyte is 0.5%;
[0083] The organic solvent is composed of ethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, and fluorinated ethylene carbonate. Based on the total volume of the organic solvent being 100%, the volume fraction of ethylene carbonate is 15%, the volume fraction of dimethyl carbonate is 30%, the volume fraction of ethyl methyl carbonate is 50%, and the volume fraction of fluorinated ethylene carbonate is 5%.
[0084] This example also provides a preparation method for the above electrolyte, and the specific method is as follows:
[0085] Under an argon atmosphere, the formulated amounts of the organic solvent, carbonate additive, sulfur-containing additive, lithium salt additive, and additive A are added to the organic solvent, and then the lithium salt is added, and the mixture is stirred at 10°C to obtain the electrolyte.
[0086] Example 2
[0087] The difference between Example 2 and Example 1 is:
[0088] The mass percentage of additive A in the electrolyte is 0.2%, and the rest is the same as in Example 1.
[0089] Example 3
[0090] The difference between Example 3 and Example 1 is:
[0091] The mass percentage of additive A in the electrolyte is 0.8%, and the rest is the same as in Example 1.
[0092] Example 4
[0093] The difference between Example 4 and Example 1 is:
[0094] The mass percentage of additive A in the electrolyte is 2.0%, and the rest is the same as in Example 1.
[0095] Example 5
[0096] The difference between Example 5 and Example 1 is:
[0097] Additive A is 2-(2-ethyl-1H-imidazol-1-yl)acetonitrile, and the rest is the same as in Example 1.
[0098] Example 6
[0099] The difference between Example 6 and Example 1 is:
[0100] Additive A is 1H-imidazole-1-carbonitrile, and the rest is the same as in Example 1.
[0101] Example 7
[0102] The difference between Example 7 and Example 1 is:
[0103] Additive A is N-(2-cyanoethyl)imidazole, and the rest is the same as in Example 1.
[0104] Example 8
[0105] The difference between Example 8 and Example 1 is:
[0106] Additive A is 1-cyanoethyl-2-methylimidazole, and the rest is the same as in Example 1.
[0107] Example 9
[0108] The difference between Example 9 and Example 1 is:
[0109] Additive A is 2-(2-methyl-1H-imidazol-1-yl)acetonitrile, and the rest is the same as in Example 1.
[0110] Example 10
[0111] The difference between Example 10 and Example 1 is:
[0112] The mass percentage of lithium difluorobisoxalatoborate in the electrolyte is 0, and the rest is the same as in Example 1.
[0113] Embodiment 11
[0114] The difference between Example 11 and Example 1 is that:
[0115] The mass percentage of vinylene carbonate in the electrolyte is 0, and the rest is the same as in Example 1.
[0116] Example 12
[0117] The difference between Example 12 and Example 1 is:
[0118] The mass percentage of vinyl sulfate in the electrolyte is 0, and the rest is the same as in Example 1.
[0119] Embodiment 13
[0120] The difference between Example 13 and Example 1 is that:
[0121] The mass percentage of additive A in the electrolyte is 3%, and the rest is the same as in Example 1.
[0122] Comparative Example 1
[0123] The difference between Comparative Example 1 and Example 1 is:
[0124] The electrolyte does not contain additive A, and the rest is the same as in Example 1.
[0125] Comparative Example 2
[0126] The difference between Comparative Example 2 and Example 1 is:
[0127] Additive A is replaced by imidazole, and the mass percentage of imidazole in the electrolyte is 0.5%. The rest is the same as in Example 1.
[0128] Comparative Example 3
[0129] The difference between Comparative Example 3 and Example 1 is:
[0130] The additive A is replaced by imidazole and acetonitrile, and the mass percentage of imidazole and acetonitrile in the electrolyte is 0.5%. The rest is the same as in Example 1.
[0131] Comparative Example 4
[0132] The difference between Comparative Example 4 and Example 1 is:
[0133] The additive A was replaced by 2-propionitrile-1-yl-1H-imidazole-1-carboxylate, the mass percentage of 2-propionitrile-1-yl-1H-imidazole-1-carboxylate in the electrolyte was 0.5%, and the rest was the same as in Example 1.
[0134] Test Method
[0135] The electrolytes prepared in Examples 1 to 13 and Comparative Examples 1 to 4 were applied to lithium-ion batteries, and the performance of the lithium-ion batteries was tested. The specific preparation method of the lithium-ion battery used for the test includes: preparing a slurry of negative electrode material graphite, conductive agent acetylene black and binder carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) in a mass percentage of 94:1:2:3, coating the slurry on a copper foil current collector, and vacuum drying to obtain a negative electrode sheet; preparing a positive electrode material NCM613 (LiNi 0.6 Co 0.1 Mn 0.3 O2), conductive agent acetylene black and binder polyvinylidene fluoride (PVDF) were prepared into a slurry in a mass ratio of 94:3:3 and coated on an aluminum foil current collector, and vacuum dried to obtain a positive electrode sheet. The positive electrode sheet, negative electrode sheet, separator and electrolyte prepared in the embodiment or comparative example were assembled into a soft-pack battery, and electrochemical tests were performed using a Xinwei charge and discharge test cabinet, and the hydrofluoric acid (HF) content in the electrolyte was determined by ice water titration.
[0136] (1) Cycle performance test of lithium-ion batteries:
[0137] At 45°C, the lithium-ion battery is charged at a constant current of 1C (nominal capacity) to a voltage of 4.4V, then charged at a constant voltage of 4.4V to a current ≤ 0.05C, left for 30 minutes, and then discharged at a constant current of 1C to a cut-off voltage of 2.8V. The above is one charge and discharge cycle. The lithium-ion battery is subjected to 1000 charge and discharge cycles at 45°C under the above conditions.
[0138] The capacity retention rate (%) of a lithium-ion battery after N cycles = (discharge capacity at the Nth cycle / initial discharge capacity) × 100%, where N is the number of cycles of the lithium-ion battery.
[0139] (2) Electrolyte HF content test:
[0140] The electrolyte was stored at 60°C, and the HF contents at 0d and 20d were measured by ice water titration, respectively, and recorded as HF-0d and HF-20d.
[0141] (3) High temperature storage performance test of lithium-ion batteries:
[0142] At 25°C, the lithium-ion battery was charged at a constant current of 0.33C to a voltage of 4.4V, and then charged at a constant voltage of 4.4V to a current of 0.05C. The volume of the tested lithium-ion battery was V0, and the initial capacity was C0. The lithium-ion battery was then placed in a constant temperature box at 60°C and stored for 90 days, and the volume of the tested lithium-ion battery was taken out and recorded as V1, the capacity remained C1, and the capacity recovered to C2.
[0143] The volume expansion ratio (%) of a lithium-ion battery after storage at 60°C for 90 days = (Vn-V0) / V0×100%.
[0144] The capacity retention rate (%) of the lithium-ion battery after storage at 60°C for 90 days = (C1 / C0)×100%, and the capacity recovery rate (%) of the lithium-ion battery after storage at 60°C for 90 days = (C2 / C0)×100%.
[0145] The test results are shown in Table 1 below:
[0146] Table 1
[0147]
[0148]
[0149] According to the test results in Table 1, the electrolyte provided in the embodiment contains additive A, which can participate in the positive electrode film formation and the negative electrode film formation, reduce the dissolution of transition metal ions in the positive electrode material, improve the stability of the structure of the positive electrode material and the negative electrode material, reduce the battery cycle impedance, and improve the battery cycle performance; in addition, by adding additive A to the electrolyte, the increase in electrolyte acidity can be effectively suppressed, the high-temperature performance deterioration caused by acid release in the high-voltage system can be improved, and the high-temperature storage performance of the battery can be improved.
[0150] It can be seen from the analysis of Examples 1-4 and 10-12 that: adding a lithium salt additive to the electrolyte has the function of forming a film at the positive and negative electrodes, and the generated solid electrolyte interface film is relatively dense, which can inhibit the dissolution of metal ions at the positive electrode, weaken the damage of additive A and metal ions to the solid electrolyte interface film at the negative electrode, and thus reduce the deterioration of additive A on the negative electrode, and improve the stability of film formation; adding a sulfur-containing additive to the electrolyte can assist in film formation at the positive and negative electrodes, and has high thermal stability; adding a carbonate additive to the electrolyte can form a film at the negative electrode. The present invention can further improve the high-temperature storage performance and cycle performance of the battery by adding carbonate additives, sulfur-containing additives, lithium salt additives and additive A, and utilizing the synergistic effect between the additives.
[0151] From the analysis of Examples 1-4 and Example 13, it can be seen that by controlling the mass percentage of additive A in the electrolyte in the range of 0.2%-2.0%, the addition of A can effectively adsorb water, phosphorus pentafluoride, hydrofluoric acid and other substances while reducing the battery impedance, which is more conducive to simultaneously improving the battery's cycle performance and high-temperature storage performance.
[0152] Analysis of Examples 5-9 and Comparative Example 4 shows that the nitrogen atom on the imidazole ring in Additive A is directly connected to groups such as cyano, cyanoethyl or dimethylene cyano, which is more conducive to Additive A improving the cycle performance and high temperature storage performance of the battery.
[0153] The embodiments of the present invention are described in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.
Claims
1. An electrolyte, characterized in that: The electrolyte includes an organic solvent, an additive and a lithium salt, wherein the additive includes an additive A, and the structure of the additive A is shown in Formula I: wherein n is selected from 0, 1, 2, 3, 4, 5 or 6; The substituents R1, R2 and R3 are each or independently selected from a hydrogen atom, a halogen, a cyano group, an isocyanate group, a C1-C10 straight or branched alkyl group, a C1-C10 straight or branched alkoxy group, a C1-C10 halogenated straight or branched alkyl group, a C1-C10 halogenated straight or branched alkoxy group, a C3-C10 straight or branched carboxylate group, a C3-C10 straight or branched alkenyl group, a C3-C10 straight or branched alkynyl group, a C6-C26 unsubstituted aryl group, a C6-C26 aryl group substituted by an alkyl group, a hydroxyl group and / or a halogen group, a C7-C27 unsubstituted benzyl group, a C7-C27 benzyl group substituted by an alkyl group, a hydroxyl group and / or a halogen group, or a combination of these groups.
2. The electrolyte according to claim 1, characterized in that The n is selected from 0, 1 or 2; and / or The substituents R1, R2 and R3 are each or independently selected from a hydrogen atom and / or a C1-C2 straight-chain alkyl group.
3. The electrolyte according to claim 1 or 2, characterized in that The mass percentage of the additive A in the electrolyte is 0.2%-2.0%; and / or The additive A is selected from at least one of imidazole-1-ylacetonitrile, 2-(2-methyl-1H-imidazol-1-yl)acetonitrile, 2-(2-ethyl-1H-imidazol-1-yl)acetonitrile, 1H-imidazole-1-carbonitrile, N-(2-cyanoethyl)imidazole, and 1-cyanoethyl-2-methylimidazole.
4. The electrolyte according to claim 1 or 2, characterized in that The additives also include carbonate additives, sulfur-containing additives and lithium salt additives.
5. The electrolyte according to claim 4, characterized in that The mass percentage of the carbonate additive in the electrolyte is 0.2%-1.0%; and / or The mass percentage of the sulfur-containing additive in the electrolyte is 0.2%-2.0%; and / or The mass percentage of the lithium salt additive in the electrolyte is 0.5%-2.0%; and / or The carbonate additive includes at least one of vinylene carbonate, fluoroethylene carbonate and vinyl carbonate; and / or The sulfur-containing additive includes at least one of 1,3-propane sultone, 1,3-propylene sultone, vinyl sulfate, and methylene disulfonate; and / or The lithium salt additive includes at least one of lithium difluorobisoxalatoborate, lithium difluorobisoxalatophosphate, lithium bisoxalatoborate, lithium fluorosulfonyl imide, lithium difluorophosphate, and lithium tetrafluoroborate.
6. The electrolyte according to claim 1 or 2, characterized in that The mass percentage of the lithium salt in the electrolyte is 10%-16%; and / or The lithium salt includes at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide and lithium tetrafluoroborate.
7. The electrolyte according to claim 1 or 2, characterized in that: The organic solvent includes at least two of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and fluoroethylene carbonate.
8. The electrolyte according to claim 7, characterized in that In the organic solvent, the volume fraction of ethylene carbonate is 0-30%, the volume fraction of propylene carbonate is 0-20%, the volume fraction of dimethyl carbonate is 0-40%, the volume fraction of diethyl carbonate is 0-20%, the volume fraction of ethyl methyl carbonate is 0-50%, and the volume fraction of fluoroethylene carbonate is 0-20%.
9. A method for preparing an electrolyte according to any one of claims 1 to 8, characterized in that: The following steps are involved: Under a protective atmosphere, uniformly mixing a formulated amount of an organic solvent, a lithium salt and an additive to obtain the electrolyte; Wherein, the additive includes additive A.
10. The method for preparing an electrolyte according to claim 9, characterized in that: The order of adding the mixed raw materials is adding the additive to the organic solvent and then adding the lithium salt; and / or The protective atmosphere comprises a nitrogen atmosphere and / or an argon atmosphere; and / or The additives also include carbonate additives, sulfur-containing additives and lithium salt additives.
11. A lithium ion battery, characterized in that: The lithium-ion battery comprises the electrolyte according to any one of claims 1 to 8.
12. The lithium ion battery according to claim 11, characterized in that: The lithium-ion battery also includes a positive electrode, a negative electrode and a separator; The active material of the positive electrode is a nickel-cobalt-manganese ternary material; and / or The active material of the negative electrode is graphite or silicon carbon.
13. The lithium ion battery according to claim 12, characterized in that: The chemical formula of the nickel-cobalt-manganese ternary material is: Li(Ni x Co y Mn z )O2, where 0.5 ≤ x < 0.9, 0 < y ≤ 0.3, 0 < z ≤ 0.3, and x + y + z = 1.
Citation Information
Patent Citations
Lithium ion battery electrolytic solution for promoting graphite cathode film formation and lithium ion battery made by the same
CN101345325A
Electrolyte composition, secondary battery, and method for using secondary battery
CN106575791A
Imidazolium-based ionic liquid and preparation method and application thereof
CN108586348A
High-temperature stable electrolyte and lithium ion battery thereof
CN110061291A
Lithium cobalt oxide high-voltage lithium ion battery non-aqueous electrolyte and lithium ion battery
CN113394450A
Cited By
Lithium battery composite diaphragm, preparation method thereof and lithium battery
CN121394769A